2018
DOI: 10.1109/tmi.2018.2791179
|View full text |Cite
|
Sign up to set email alerts
|

High-Permittivity Pad Design for Dielectric Shimming in Magnetic Resonance Imaging Using Projection-Based Model Reduction and a Nonlinear Optimization Scheme

Abstract: Abstract-Inhomogeneities in the transmit RF magnetic field (B + 1 ) reduce the quality of MR images. This quality can be improved by using high-permittivity pads that tailor the B + 1 fields. The design of an optimal pad is application-specific and not straightforward, and would therefore benefit from a systematic optimization approach. In this paper, we propose such a method to efficiently design dielectric pads. To this end, a projection based model order reduction technique is used that significantly decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) [1] is an essential medical diagnostic tool which is used for observing the tissue changes of the patients in the absence of ionizing radiation. It provides high-resolution images that contain important anatomical information.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) [1] is an essential medical diagnostic tool which is used for observing the tissue changes of the patients in the absence of ionizing radiation. It provides high-resolution images that contain important anatomical information.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we note that the stability of our solution against a range of w b values implies the robustness of our evanescent mode-shaping solution to the shape or displacement of the used phantom. In the optimization process, only three factors (effectively two) need to be considered for homogenization, which is less complex than the pad optimization scheme in other studies 30 , 31 .
Figure 4 Effects of the air-gap potential barrier width w b on the mode.
…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the pad design domain was divided into small subdomains, on average 2.5 cm in width and 2.3 cm in height, by assigning the same material properties to grid edges that belong to a given non‐overlapping subdomain. To exploit the reduced solution space because of the subdomains and the parameterization, a reduced order model was created following the procedure described in van Gemert et al In this same work, it was shown that the reduced order model produces a negligible error. This allows for field computations that are up to 4 orders of magnitude faster than conventional EM solvers such as XFdtd.…”
Section: Methodsmentioning
confidence: 99%
“…In previous works, we have developed an advanced reduced order modeling technique to accelerate pad evaluations by characterizing stationary components such as the RF coil and body model in an offline‐stage and compressing the resulting model. This yielded up to 4 orders of magnitude of acceleration compared to commercial software and enabled the automated design of dielectric pads in under 1 min . The resulting framework is, however, body‐model‐specific, and optimization results obtained in a generic model are not likely to be optimal when the subject anatomy is substantially different, particularly in the case of fetal imaging.…”
Section: Introductionmentioning
confidence: 99%